2019
DOI: 10.1080/13696998.2018.1559600
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of the SAPIEN 3 TAVI valve compared with surgery in intermediate-risk patients

Abstract: Objective: Transcatheter aortic valve implantation (TAVI) has become the therapy of choice for treating severe aortic stenosis in patients at high-risk for surgery or where it is considered too risky to attempt. This uptake varies across geographies however, and its cost or value has frequently been cited as the reason for this. We sought to evaluate the potential cost and clinical impact of TAVI in intermediate risk patients from a French collective perspective. Materials and methods: The analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Models in patients at moderate or high risk of surgical mortality comprised Markov models based around complications or New York Heart Association class. 16,17 The New York Heart Association class was not judged granular enough to capture the differences between treatments in patients at low risk of surgical mortality, and thus, a model based around complications was used.…”
Section: Model Structurementioning
confidence: 99%
“…Models in patients at moderate or high risk of surgical mortality comprised Markov models based around complications or New York Heart Association class. 16,17 The New York Heart Association class was not judged granular enough to capture the differences between treatments in patients at low risk of surgical mortality, and thus, a model based around complications was used.…”
Section: Model Structurementioning
confidence: 99%
“…The results from the present analysis are consistent with those obtained in the few studies available related to the last generation devices. Indeed, four recent studies evaluated the CE of TAVI versus sAVR in intermediate-risk patients [24,[37][38][39]. Three of them showed TAVI being dominant considering the payer perspective and a lifetime horizon in the US [37], France [24] and Australia [39], while, accounting for the perspective of the National Health System in Canada, Tarride et al [38] found that TAVI was cost-effective (ICER being 28,154 Canadian dollars/QALY).…”
Section: Discussionmentioning
confidence: 99%
“…Transition probabilities (related to disease progression or improvement), risk of relevant clinical events and survival were derived from the Placement of Aortic Transcatheter Valves (PARTNER) trials [7,[21][22][23] and extrapolation from them all over the time horizon of the analysis as previously detailed in Goodall et al [24]; particularly, linear extrapolation was used to extend mortality data, while for complications, the last available data were assumed constant for the rest or the time period. Details of inputs for the incidence of events used in the analysis over the different risk groups and references for them are reported in Table 1.…”
Section: Clinical Datamentioning
confidence: 99%
“…Despite the fact that TAVI has already been evaluated and accepted in the health care systems of several countries with evidence of cost-effectiveness even in individuals at intermediate operative risk, 3 the Ministry of Health, based on a position stand from the National Commission for Incorporation of Technologies in the SUS (Conitec), established in 2013, in response to a request by the Brazilian Society for Hemodynamics and of Interventional Cardiology (SBHCI) acting as the petitioner, considered that there was no convenience in incorporating this therapy in Brazil. Conitec, at the time, based on the opinion of a reviewer and disregarding the opinion of prestigious national universities presented in a public consultation on the subject, recommended against the incorporation of the procedure, justifying this decision on three points: a) TAVI would not be a safe and effective procedure due to an allegedly high incidence of stroke within the first 30 days after the procedure, b) the budgetary impact of incorporating TAVI into the SUS would approach 1 billion reais per year, and c) methodological inaccuracies could have affected the economic model presented by the petitioner and the PARTNER B study, which served as the main background for the incorporation of this procedure by all health technology assessment agencies in the world that have requested the incorporation of this technology.…”
mentioning
confidence: 99%